THE EFFECT OF THE STORYTELLING METHOD ON STUDENTS’ SPEAKING SKILLS IN SENIOR HIGH SCHOOL - Hanina Zahra Al Muhdlar; Agus Milu Susetyo; Syahrul Mubaroq (LP2M IAI Al-Khairat Pamekasan, 2026)
This study seeks to assess the impact of the narrative pedagogical approach on the speaking abilities of tenth-grade students at SMAN Pakusari Jember. This research is predicated on the students' inadequate speaking proficiency, as seen by their diminished confidence and participation in oral communication. This study utilized a quantitative methodology using a one-group pretest-posttest experimental design. The participants comprised 29 kids in the tenth grade. The research tool was a speaking proficiency assessment that evaluated fluency, linguistic precision, and self-assurance in public speaking. Data were assessed by descriptive and inferential statistics to evaluate enhancement following the application of the storytelling method. The findings indicated a notable enhancement in students' speaking proficiency following the implementation of storytelling. Students exhibited increased confidence, fluency, and the capacity to articulate concepts logically. Consequently, the storytelling approach has been demonstrated to be an effective alternative instructional tool for improving students' speaking skills in the Indonesian language.